Prevalence and risk factors of hearing loss in high-risk neonates at a tertiary care hospital in Mumbai - Pradhan, Monalisa; Bhaisara, Baraturam; Shinde, Srinivas Rao G. (International Journal of Contemporary Pediatrics, 2023)
Background: The present study was conducted to assess the prevalence of hearing loss using measurements of otoacoustic emission (OAE) in newborns admitted to NICU and to determine the risk factors predictive of hearing impairment in these newborns. Methods: This was a Prospective observational study conducted among 220 newborns admitted to the NICU over 18 months. Ethical clearance was obtained from the IEC. The sample size was obtained by the universal sampling technique. All candidates underwent hearing assessment in a sound-treated room in the department using a distortion product OAEs (DPOAE) test at the time of discharge. Babies who did not pass the initial screening underwent another OAE test within one month after being discharged. If they failed the test again, they were referred to an otologist for BERA. Results: Of the 226 neonates included in the study, 40 cases (17.7%) failed the initial screening. 29 cases (12.8%) failed the second OAE screening and were subjected to BERA. Risk factors included asphyxia (p≤0.001), mechanical ventilation (p<0.0004), history of ototoxic medication (p=0.004), neonates with hyperbilirubinemia requiring exchange transfusion (p=0.005), low Apgar scores (p≤0.001). Conclusions: A two-stage OAE hearing screening can be a suitable method for early detection of hearing impairment in newborns. This method has shown high prevalence of hearing loss among high-risk neonates but needs to be confirmed with diagnostic BERA. It is crucial to have universal hearing screening to detect the large number of hearing-impaired neonates in the newborn population of our country, including those who are not considered at risk.